Pengolahan Air Minum Sistem Reverse Osmosis di Pesantren Hidayatullah Gowa. - Muhammad Syahid; Mukhtar Rahman -; Nasruddin Azis -; Syahrier Arief; Irwan Fathar (Faculty of Engineering UNHAS, 2019)
This activity aims to improve the quality of drinking water with a reverse osmosis system that is water filtration treatment to neutralize the taste, odor and hazardous substances contained in water up to 0,0001 microns. One obstacle faced by Hidayatullah Islamic Boarding School, Timbuseng Village, Pattalassang Subdistrict, Gowa Regency is very dependent on traditional management and the use of gallon water supply services, so that it requires a lot of energy and a long time and high costs if provided by buying gallon water . With Community Service Activities this reverse osmosis assistance is expected to be an alternative supply of drinking water that is suitable for consumption so that staff / students can avoid the risk of disease and make time and money spent to buy gallon water efficient.